Homotopy perturbation method for predicting tsunami wave propagation with crisp and uncertain parameters. Issue 1 (1st May 2020) - Karunakar, Perumandla; Chakraverty, Snehashish
Abstract : Purpose: The purpose of this paper is to find the solution of classical nonlinear shallow-water wave (SWW) equations in particular to the tsunami wave propagation in crisp and interval environment. Design/methodology/approach: Homotopy perturbation method (HPM) has been used for handling crisp and uncertain differential equations governing SWW equations. Findings: The wave height and depth-averaged velocity of a tsunami wave in crisp and interval cases have been obtained. Originality/value: Present results by HPM are compared with the existing solution (in crisp case), and they are found to be in good agreement. Also, the residual error of the solutions is found for the convergence conformation and reliability of the present results.